FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK DAERAH PROVINSI KALIMANTAN TIMUR - Mat Juri; Achmad Rudzali; Verawati Verawati (Jurnal Eksis, 2019)
The purpose of the study is to determine the influence of independent variables, namely inflation, Gross Regional Domestic Product (GRDP), number of moter vehicles and the population to local tax revenues in East Kalimantan Province in 2007-2018. The results of this study showed that variable population counts had a positive but insignificant influence on regional tax revenues, whereas the GRDP variable had a negative and insignificant influence on local tax revenues. The variable number of motor vehicles and inflation has a positive and significant influence on the regional tax revenues of East Kalimantan Province. Econometrics test result also showed that the absense of interference with multicholininearality, autocorrelation disorder and heteroskedastisity disorders. Keywords:Tax Revenues, Inflation, Gross Regional Domestic Product, Number of Registered Motor Vehicles, and Number of Population.